An Information System for Ambulatory Care - Garratt, Alfred E. (1979)
The Indian Health Service operates a complex, multi-level, physically dispersed health delivery system in providing health care to approximately 750,000 American Indians and Alaska Natives. To support the delivery of comprehensive health care and to provide for continuity of care in this environment, the IHS has designed, developed and is now field testing the Patient Care Information System.